Micromechanical Formulation of the Yield Surface in the Plasticity of Granular Materials. (22nd September 2013) - Shaverdi, Homayoun; Taha, Mohd. Raihan; Kalantary, Farzin
Abstract : An equation is proposed to unify the yield surface of granular materials by incorporating the fabric and its evolution. In microlevel analysis by employing a Fourier series that was developed to model fabric, it is directly included in the strength of granular materials. Inherent anisotropy is defined as a noncoaxiality between deposition angle and principal compressive stress. Stress-induced anisotropy is defined by the degree of anisotropy α and the major direction of the contact normals. The difference between samples which have the same density (or void ratio) but different bedding angles is attributed to this equation. The validity of the formulation is verified by comparison with experimental data.